2003
DOI: 10.1111/j.1365-2591.2003.00722.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitric oxide synthase inhibitor (L‐NAME) on substance P‐induced vasodilatation in the dental pulp

Abstract: This study demonstrates that NOS inhibitor L-NAME administration alone has insignificant effects on pulpal blood flow, although L-NAME pretreatment can potentiate SP-induced vasodilatation, probably via increased activity in the enzyme guanylate cyclase. CGRP and papaverine did not respond to L-NAME pretreatment, indicating that they are not mediated via an endothelium-dependent mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…For example, another group concluded that l-NAME treatment alone has no obvious effects on pulpal blood flow in the feline lingual artery, nor does l-NAME pretreatment affect the actions of multiple vasodilators, such as substance P; these findings suggest that these processes are not mediated through an endothelium-dependent mechanism. 82 Moreover, previous studies have identified the effective regulation of neurons on dental pulp microcirculation under physiological and pathological conditions. 83,84 Similarly, eNOS-mediated pulp vasodilation is also a valuable response in neurogenic inflammation and involves subsequent release of NO produced in endothelial cells and of inflammatory mediators (e.g., substance P) from sensory nerve endings.…”
Section: Anmentioning
confidence: 99%
“…For example, another group concluded that l-NAME treatment alone has no obvious effects on pulpal blood flow in the feline lingual artery, nor does l-NAME pretreatment affect the actions of multiple vasodilators, such as substance P; these findings suggest that these processes are not mediated through an endothelium-dependent mechanism. 82 Moreover, previous studies have identified the effective regulation of neurons on dental pulp microcirculation under physiological and pathological conditions. 83,84 Similarly, eNOS-mediated pulp vasodilation is also a valuable response in neurogenic inflammation and involves subsequent release of NO produced in endothelial cells and of inflammatory mediators (e.g., substance P) from sensory nerve endings.…”
Section: Anmentioning
confidence: 99%
“…However, NO synthase inhibitor potentiates SP-induced vasodilatation in vivo. This unexpected result may be due to a negative feedback mechanism, which needs to be verified by further experiments (Hsu et al 2003).…”
Section: Regulation Of Blood Vessels In Pulpitismentioning
confidence: 87%
“…This unexpected result may be due to a negative feedback mechanism, which needs to be verified by further experiments (Hsu et al . 2003).…”
Section: Neuromodulation In Pulpitismentioning
confidence: 99%
“…6 Particularly, iNOS produces much larger amounts of nitric oxide and has been detected in many inflammatory diseases, including those affecting oral tissues. 7 However, data about the real significance of iNOS expression European Journal of Dentistry in periapical cysts following inflammatory process are fairly limited in literature. 8,9 As a result of limited evidence, the present study was undertaken to investigate if inducible nitric oxide expression (iNOS) is correlated with the level of inflammation in periapical cysts.…”
mentioning
confidence: 99%